PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA PEGAWAI DI DIREKTORAT SEREALIA DIREKTORAT JENDERAL TANAMAN PANGAN KEMENTERIAN PERTANIAN - Heny Sulistyani; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
performance values and achievement values of civil servant performance at Directorate of Cereal in the Ministry of Agriculture, and it was supported previously research by Harits Syah. This Research aims to analyzed the influence of financial compensation toward performance of employees in directorate of cereal grains, Ministry of Agriculture. There are two variable used in this research, they are Independent variable (financial compensation) and dependent variable (performance).The problem formulation and the purposed this research are compensation had possitive and signification influence toward civil servant performance of employees in Directorate of Cereal Ministry of Agriculture.This research used a quantitative approach. Which is more emphasis on indexes and empirical measurement. This research used explanatory riset, where as hypothesis testing technique used linear regression analysis and T test.The result of this research concluded that there aren’t possitive and significant influence of financial compensation toward civil servant performance at Directorate of Cereal in Ministry of Agriculture. It means that if financial compensation was increased, the performance of civil servant will increase as well. Where as the great score of precentage financial compensation and civil servant performance at Directorate of Cereal Ministry of Agriculture includes in excelent catagory.